Nursing professionals' knowledge of preparing and administering insulin to hospitalized children and adolescents - Sarah Arrais de Lavor; Fernanda Jorge Magalhães; Andreia Ferreira Soares; Roberta Meneses Oliveira; Sherida Karanini Paz de Oliveira (Universidade Federal do Ceará, 2024)
Objective: to describe nursing professionals' knowledge of preparing and administering insulin to hospitalized children and adolescents. Methods: a cross-sectional study with 64 nursing professionals from a highly complex public children's hospital, recruited by convenience sampling. A questionnaire was used to collect data, and the level of professional knowledge and the quality of care were analyzed using the positivity index. The ethical and legal principles of research were complied with. Results: there was a predominance of women (94.4%) with an average age of 37.16+8.09 years and an average time working in pediatrics of 13.90+8.91 years. Of the 19 items on insulin, those considered poor assistance (eight) prevailed, followed by borderline assistance (five), which may have an impact on the preparation and administration of insulin with glycemic and metabolic repercussions for pediatric inpatients. Conclusion: weaknesses were found concerning nursing professionals' knowledge of various aspects of insulin use in children and adolescents in the hospital environment. Contributions to practice: the study addresses gaps in the nursing team's knowledge of insulin injection, providing opportunities for improvement.